2015
DOI: 10.1038/bcj.2015.84
|View full text |Cite
|
Sign up to set email alerts
|

Single monosomy as a relatively better survival factor in acute myeloid leukemia patients with monosomal karyotype

Abstract: on behalf of the Korean Society of Hematology AML/MDS Working Party Monosomal karyotype (MK) defined by either ⩾ 2 autosomal monosomies or single monosomy with at least one additional structural chromosomal abnormality is associated with a dismal prognosis in patients with acute myeloid leukemia (AML). It was detected in 174 of 3041 AML patients in South Korean Registry. A total of 119 patients who had received induction therapy were finally analyzed to evaluate the predictive factors for a positive prognosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…The 2-year cumulative incidence of relapse was 36.7% for the "-7/7q-± CK group," 47.8% for the "MK group," 51% for the "-5/5qgroup," 62.9% and 68.4% for the "inv(3) group" (P < .001, Figure 2A), which translated into a 2-year probability of LFS of 48%, 36.4%, 28.4%, 19.1% and 17.3% for the "-7/7q-± CK," "MK," "-5/5q-," "abn(17p)" and "inv(3)" groups, respectively (P < .001, Figure 2C). The 2-year NRM was similar across our five cytogenetic <.0001 20 (16)(17)(18)(19)(20)(21)(22)(23)(24) .99 23 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27) <.0001 27 (22)(23)(24)(25)(26)(27)(28)(29)(30)(31) <.0001 13 (10)(11)(12)(13)(14)(15)(16) <.0001 26 (22)(23)(24)(25)(26)(27)(28)(29)…”
Section: Outcomes By Cytogenetic Subgroupsmentioning
confidence: 62%
See 1 more Smart Citation
“…The 2-year cumulative incidence of relapse was 36.7% for the "-7/7q-± CK group," 47.8% for the "MK group," 51% for the "-5/5qgroup," 62.9% and 68.4% for the "inv(3) group" (P < .001, Figure 2A), which translated into a 2-year probability of LFS of 48%, 36.4%, 28.4%, 19.1% and 17.3% for the "-7/7q-± CK," "MK," "-5/5q-," "abn(17p)" and "inv(3)" groups, respectively (P < .001, Figure 2C). The 2-year NRM was similar across our five cytogenetic <.0001 20 (16)(17)(18)(19)(20)(21)(22)(23)(24) .99 23 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27) <.0001 27 (22)(23)(24)(25)(26)(27)(28)(29)(30)(31) <.0001 13 (10)(11)(12)(13)(14)(15)(16) <.0001 26 (22)(23)(24)(25)(26)(27)(28)(29)…”
Section: Outcomes By Cytogenetic Subgroupsmentioning
confidence: 62%
“…14,15 Within MK, the presence of monosomy 7 alone did not show any independent impact on survival. 14,16 However, in the transplant setting, a retrospective study from the EBMT addressing SCT for MK AML showed that monosomy 7 retained a significant impact on outcomes. 17 We recently reported the outcome of 125 patients with AML and 17p abnormalities (abn(17p)) transplanted in first remission.…”
Section: Introductionmentioning
confidence: 99%
“…A single monosomy has resulted in better prognosis and PFS, and thus, remained as a significantly independent prognostic factor for patients both treated or untreated with allo-HSC transplantation [127]. However, biological mechanism of single MK could be different from 2 or more MK, which needs further evaluation on both AML and MDS.…”
Section: Complex Chromosomal Aberrations (Ck) and Monosomal Karyotypementioning
confidence: 99%
“…70,71 In fact, a linear trend between CAs in PBLs and subsequent cancer risk has been shown by several prospective cancer studies. 29,[72][73][74][75] CEP2,CEP8,CEP11 CEP3,CEP15,CEP17 Exposed Unexposed Figure 5 Representative FISH images of an exposed and an unexposed individual. Metaphase spreads are shown and boxes indicate representative interphase nuclei for each case.…”
Section: Cin (%)mentioning
confidence: 99%